The Dynamics of Workplace Bullying: Behavioral Indicators and Organizational Implications Among Non-Teaching Personnel in the Schools Division Office of the Department of Education, City Schools Division of Cabuyao - Dalce, Shiela G.; Dugang, Eva Claire P.; Pansa, Clyn Roche S.; Manzanero, Jhoanna M.; Malang, Bernandino P.; Malang, Jocelyn DS. (Future Science / FSH-PH Publications, 2026)
The research entitled “The Dynamics of Workplace Bullying: Behavioral Indicators and Organizational Implications among Non-Teaching Personnel in the Schools Division Office of the Department of Education, City Schools Division of Cabuyao” explores how bullying happens in an educational workplace and among non-teaching personnel. The main goal was to understand what were the behavioral aspects that ignites to bullying in workplace setting and how these affect the people who experience it as well as its organizational implication, while indeed, identifying strategies or interventions to promote a healthy and safe working environment within the workplace in mitigation to bullying. The study used descriptive-explanatory sequential mixed- methods research design and gathered data from 77 respondents through an online survey questionnaire followed by a semi-structured interview among 10 non-teaching staff. Findings showed that behavioral indicators of workplace bullying such as verbal and psychological abuse; social exclusion or isolation; work-related harassment; and cyberbullying and digital harassment have a significant impact and implication to the organization in as much as job satisfaction and morale, psychological well-being and stress, team collaboration and organizational climate, and employee retention and turnover intention were concerned. Results also highlighted that these variables were contributory for the organizations efficiency in general. Workplace bullying, though rarely experienced, still exhibited in various injurious forms that significantly affect employee well-being and organizational performance. This underscored the significance of instigating proactive policies and support systems to ensure a healthy, safe, respectful, and productive work environment for employees and people in the organization.